PAMAM Dendrimer‐Based Nanodevices for Nuclear Medicine Applications - Xiao, Tingting; Li, Du; Shi, Xiangyang; Shen, Mingwu (Macromolecular bioscience, 2020)
Nuclear medicine, involving nuclear medicine imaging and radiotherapy (RT), has become a mainstay of theranostics in the field of nanomedicine and several examples have been successfully translated into clinical practice. The combination of radionuclides with dendrimers has long been investigated in nuclear imaging, such as positron emission tomography (PET) and single‐photon emission computed tomography (SPECT), providing functional information for whole body quantitative analysis with high sensitivity due to the unique structural advantages of the dendrimer platform. Besides, radioisotopes with both therapeutic and imaging functionalities can also be combined with dendrimer platforms for theranostic applications. In this review, the recent advances in the development of radionuclide‐labeled poly(amidoamine) dendrimer‐based nanodevices for targeted PET, SPECT, SPECT/computed tomography, SPECT/magnetic resonance imaging of tumors, RT, as well as for SPECT‐imaging‐guided RT of cancer are summarized. Current restrictions hindering the clinical translation of dendrimer‐based nuclear nanodevices and future prospects are also discussed. Poly(amidoamine) (PAMAM) dendrimers have been employed as a powerful platform to be multifunctionalized through their periphery and internal cavities. This review summarizes the recent progresses in the development of radionuclide‐labeled PAMAM dendrimer‐based nanodevices for targeted positron emission tomography (PET), single‐photon emission computed tomography (SPECT), SPECT/computed tomography (CT), SPECT/magnetic resonance imaging, PET/CT imaging, radiotherapy, and nuclear imaging‐guided radiotherapy of cancer.